PEMBINAAN AKUNTANSI PADA KOPERASI MASYARAKAT TANJUNG GUNDAP RT 02/ RW 01 KELURAHAN TEMBESI - Vargo Christian L. Tobing; Hendri Herman (PUAN INDONESIA, 2021)
Cooperative is a business entity (economic organization) owned and operated by its members to fulfill the common interests in the economic field. Given the many benefits of cooperatives, recently, the old village community of Tanjung Gundap has just formed a cooperative. This cooperative is intended so that the old kampong community of Tanjung Gundap can improve its welfare economically. The community can become a member of the cooperative and benefit from the cooperative, the community can borrow funds from the cooperative with a low interest rate so that it does not charge too much in loan payments. Because the cooperative formed by the old village community of Tanjung Gundap is still relatively new. Therefore, it is necessary to provide guidance to the community in recording finance related to cooperative operational activities. So the pengabdi team chose the theme of accounting coaching at the tanjung gundap community cooperative RT 02 / RW 01 Tembesi Village, Sagulung District. This development is intended so that cooperatives managed by the people of Tanjung Gundap have a good and correct financial record.